2018
DOI: 10.1016/j.cub.2018.02.030
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation of Puberty and Adolescent Social Development in a Seasonally Breeding Species

Abstract: Alongside the development of sexual characteristics and reproductive competence, adolescents undergo marked cognitive, social, and emotional development [1]. A fundamental question is whether these changes are triggered by activation of the hypothalamic-pituitary-gonadal (HPG) axis at puberty (puberty dependent) or whether they occur independently of HPG activation (puberty independent). Disentangling puberty-dependent from puberty-independent mechanisms is difficult because puberty and adolescence typically p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 79 publications
1
13
0
Order By: Relevance
“…This finding is consistent with a previous study showing that the total amount of adolescent social play was not influenced by pre‐pubertal ovariectomy in female rats 33 . By contrast, a recent study reported increased frequencies of play with a familiar partner following pre‐pubertal gonadectomy in female Siberian hamsters 85 . In addition, subtle aspects of posture during social interactions have been shown to be influenced by early gonadal hormone exposure in rats, 31,33 and so we cannot exclude the possibility that Antide treatment might have had more fine‐grained effects on social behaviour that were not evident in the present study.…”
Section: Discussionsupporting
confidence: 93%
“…This finding is consistent with a previous study showing that the total amount of adolescent social play was not influenced by pre‐pubertal ovariectomy in female rats 33 . By contrast, a recent study reported increased frequencies of play with a familiar partner following pre‐pubertal gonadectomy in female Siberian hamsters 85 . In addition, subtle aspects of posture during social interactions have been shown to be influenced by early gonadal hormone exposure in rats, 31,33 and so we cannot exclude the possibility that Antide treatment might have had more fine‐grained effects on social behaviour that were not evident in the present study.…”
Section: Discussionsupporting
confidence: 93%
“…In this view, the activational effects of gonadal steroids at puberty (McCarthy et al, 2012) are likely to be a recent evolutionary adaptation that reinforces sexual differentiation of the mammalian nervous system via an endocrine feedback loop. Moreover, it suggests that puberty-independent events outside the hypothalamus that contribute to behavioral maturation during mammalian adolescence, such as the transition from play to aggression in Siberian hamsters (Paul et al, 2018), could also be timed by the heterochronic pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Steroid signaling is thereby orchestrated by a range of environmental and developmental cues, which again, are highly species specific. Vertebrates include day length and/or body size information to time puberty with season and food availability ( Leka-Emiri et al, 2017 ; Paul et al, 2018 ; Hanlon et al, 2020 ), which are the most common sources for environmentally induced variation (phenotypic plasticity).…”
Section: Steroid Receptors Signalingmentioning
confidence: 99%